Bringing awareness on sustainable green manufacturing to students - Dandu, Raju (Kansas State University, 2009)
Sustainable green manufacturing is an emerging area that combines technical issues of design and manufacturing, energy conservation, pollution prevention, health and safety of communities and consumers. This presentation talks about bringing awareness and understanding of sustainable green manufacturing concepts through an assignment in MET 481 Automated Manufacturing Systems II course. Students are required to do literature research on sustainable green manufacturing, write a paper, and make a 5 minute presentation to the class on the selected topic. The selected topic is related to a specific industry such as automotive, aviation, food and beverage, pharmaceutical, petroleum refining, plastics, and energy. Students include information on issues related to drivers, barriers, laws, regulations, implementation problems, and their individual opinion on sustainable green manufacturing in the written paper.
Keywords: Sustainability; Manufacturing; Awareness; Green concepts